Solusi Recycle Sampah Organik dan Anorganik bagi Keluarga di Perumahan Taman Dramaga Permai 2 Bogor - Siti Marwiyah; Undang Undang (Institut Pertanian Bogor, 2024)
Households are one of the contributors to organic and inorganic waste. Generally, the family needs to manage waste independently. The concept of waste recycling can be applied at the household level. The aim of waste management in the Dosen Mengabdi Reguler 2022 was to provide alternative solutions for processing organic and inorganic waste in the household based on the recycling concept. The activities were carried out from July‒November 2022 in one of the villages around the IPB campus locations, namely the Taman Darmaga Permai 2, Cihideung Ilir, Ciampea, Bogor. The core activities consist of discussions and demonstrations about compost, coenzymes, re-growing vegetable plants, and the culture of mung bean sprouts from Vima 1 and Vimil 1 varieties. About 42.9% of the 14 participants sorted household waste, and 28.6% managed waste. Compost from organic waste was harvested within one month after the process, while coenzymes were harvested after three months. Ecoenzymes were attractive to all participants as a solution for processing waste. About 50% of participants favor growing vegetables and 21.4% re-grow vegetable waste. Katuk and Welsh onion plants have 100% growth and 90% survival rates. All participants had never sprouted mung bean seeds. The sprouts can be harvested 1 to 3 days after sowing as needed. The Vima 1 mung bean variety has a sweet sprout taste and produces 657.9 g of sprouts from 100 g of seeds, while the Vimil 1 taste is slightly astringent with a lower sprout production of 543.8 g.